Development of A Balinese Tradition and Rite Quiz Game With Text to Speech Feature - I Wayan Wahyu Kusuma; I Gede Partha Sindu; Ketut Agus Seputra; Putu Zasya Eka Satya Nugraha; Helmi Maulana Hadiwinata (Universitas Pendidikan Ganesha, 2025)
This research aims to develop an educational quiz-based game that presents materials on Balinese traditions and rites, equipped with an automatic question reading feature using a Natural Language Processing (NLP) approach. The method used is Research and Development (R&D) with a one-cycle Agile development approach. The application was developed using Unity, with the integration of Text-To-Speech (TTS) technology through the Tacotron 2 model to automatically generate speech from question text. Testing was conducted through four stages: functional testing using the Unity Test Framework, validation by media experts, validation by content experts, and user response testing using the User Experience Questionnaire – Short Version (UEQ-S). The results showed that the application functioned properly (100% passed), received a highly feasible rating from media experts (90%), and a very high content validity score from content experts (1.00). Meanwhile, user testing resulted in an average score of 2.33, falling into the “Excellent” category. Based on these results, it can be concluded that this educational game application is feasible to use as an interactive learning medium that is both engaging and capable of providing a positive learning experience for users.